2018
DOI: 10.1007/s13365-018-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

A composite of multisystem injury and neurocognitive impairment in HIV infection: association with everyday functioning

Abstract: The Veterans Aging Cohort Study (VACS) Index is a composite marker of multisystem injury among HIV-infected persons. We aimed to examine its cross-sectional association with functional outcomes, after considering neurocognitive impairment (NCI) and other well-established correlates of everyday functioning among HIV-infected persons. Participants included 670 HIV-infected adults (ages 18-76; 88% male; 63% non-Hispanic White; median current CD4 = 404 cells/mm; 67% on antiretroviral therapy; AIDS = 63%) enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…The most serious complication of depression in PLWH is the two-fold increased risk of mortality [11], but cognitive impairment (CI) is also an important complication, one that is associated with decreased daily function [12][13][14][15][16][17][18][19][20] and quality of life [21][22][23][24]. Meta-analyses indicates that depression is associated with ARV non-adherence (r=0.…”
Section: Introductionmentioning
confidence: 99%
“…The most serious complication of depression in PLWH is the two-fold increased risk of mortality [11], but cognitive impairment (CI) is also an important complication, one that is associated with decreased daily function [12][13][14][15][16][17][18][19][20] and quality of life [21][22][23][24]. Meta-analyses indicates that depression is associated with ARV non-adherence (r=0.…”
Section: Introductionmentioning
confidence: 99%
“…Still, there was no publication bias (Eggers intercept=7.3727, p=0.3340). Only two studies examined the impact of cognitive function on employment, with effect sizes (r=0.33) (36) and (r= -0.26) [20].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Existing literature presents con icting evidence. While some studies report that HAND has a strong in uence on medication adherence [15], ADL (16), and QOL [17], other studies have reported weak or no association between HAND and medication adherence [18], ADL [19,20], frailty [21], and QOL [22]. Two systematic reviews [3,23], have tried to synthesize existing evidence but did not conduct a meta-analysis of ndings.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of NCI include memory impairment, cognitive slowing, decreased fine motor functions and processing speed, all of which cause a significant drop in the capability to perform Activities of Daily Living (ADL). This in turn leads to an overall poor Quality of Life [ 11 ].…”
Section: Introductionmentioning
confidence: 99%